Enhancing Market Access of Smallholder Farmers: Interaction Patterns of AE Clusters with Institutional Buyers - Orlanes, Glenda Tongcua-; Baconguis, Rowena RT (Journal of Business Economics and Agribusiness, 2026)
This study examines the patterns of interaction between AE clusters and different market players as they implement various market integration strategies. Employing a case study design, the research utilized in-depth data collection from multiple sources. Primary data were gathered through key informant interviews, focus group discussions, and in-depth interviews with cooperative officers, cluster leaders, and Agroenterprise Facilitators (AEFs).The findings reveal that successful market integration of smallholder farmers requires a comprehensive approach characterized by effective communication, collaboration, trust-building, structural alignment, and strong coordination mechanisms. Establishing strategic partnerships between organized farmer groups and institutional buyers fosters sustained marketing engagement. Furthermore, collaborative efforts and cooperation among AE clusters, Agrarian Reform Beneficiaries Organizations (ARBOs), and institutional buyers are essential to achieving inclusive and sustainable market integration.